Effect of cadmium exposure during and after pregnancy of female. Issue 1 (31st December 2023) - Ali, Waseem; Bian, Yusheng; Zhang, Hao; Qazi, Izhar Hyder; Zou, Hui; Zhu, Jiaqiao; Liu, Zongping
ABSTRACT: Cadmium is a common environmental pollutant and used for industrial purposes all over the world. Cadmium exposure causes a variety of public health issues, mainly reproductive health. The present review discusses the information related to female reproductive health, including during and after pregnancy and its outcomes. Cadmium alters steroidogenesis, delays puberty, causes pregnancy loss of reproductive hormones, disturbs the menstrual cycle, causes premature births, and reduces birth weights in females. Besides that, their offspring are affected differently by prenatal mother exposure to cadmium, with more female offspring being distressed. During lactation period, nursing babies fed with milk containing cadmium causes disparity in brain physiology, reflex changes and physical immaturity. Together, these reviews highpoint the need for more studies into the consequences of cadmium exposure on reproductive health.